Van Houlten’s Impoliteness in John Green’s Novel “The Fault in our Stars” - Naser, Afraa Abdulhussein; Hameed, Sarab Khalil (Al-Adab Journal, 2023)
Impoliteness is an act that is rejected and refused in the conventions of any society. However, it is utilized occasionally for various hidden motives and not only as an act of threatening others’ faces. This act is ascertained to be systematic according to Culpeper’s ‘Anatomy of impoliteness which is the adopted model in the present study. This model is applied to demonstrate the strategies that John Green adopts to demonstrate Van Houlten’s character that acts impolitely Green’s novel “The Fault in our Stars. The present study intends to reveal the types of impolite strategies that the writer utilizes to indicate this act of impoliteness and it also intend to reveal that impoliteness is a means to express grief, anger, and despair of life when losing our beloved.